2021
DOI: 10.1108/bfj-03-2021-0275
|View full text |Cite
|
Sign up to set email alerts
|

Cooperatives' performance relative to investor-owned firms: a non-distorted approach for the wine sector

Abstract: Purpose This study aims to investigate whether significant performance differences between cooperatives and investor-owned firms (IOFs) may exist.Design/methodology/approach Based on data from a sample of Italian wine firms for the period from 2009 to 2018, an adjusted measure of performance called earnings before interests, taxes, depreciations and amortizations gross the raw materials cost was adopted to consider the different objectives of cooperatives relative to those of IOFs.Findings Empirical evidence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 63 publications
0
5
0
1
Order By: Relevance
“…Unfortunately, the COVID-19 pandemic has completely changed the situation in the tourism sector (Yeh, 2020). For example, in Italy, which is the most productive country in the world in the wine sector and with other relevant records that set it as most probably the most relevant country in the world concerning wine (D'Amato et al. , 2021; Smyczek et al.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the COVID-19 pandemic has completely changed the situation in the tourism sector (Yeh, 2020). For example, in Italy, which is the most productive country in the world in the wine sector and with other relevant records that set it as most probably the most relevant country in the world concerning wine (D'Amato et al. , 2021; Smyczek et al.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Unfortunately, the COVID-19 pandemic has completely changed the situation in the tourism sector (Yeh, 2020). For example, in Italy, which is the most productive country in the world in the wine sector and with other relevant records that set it as most probably the most relevant country in the world concerning wine (D'Amato et al, 2021;Smyczek et al, 2020), the economic expansion of wine tourism was sharply arrested in the more critical COVID-19 period, because of the limitations imposed on movements due to the lockdowns.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Więzi pionowe między członkami spółdzielni a przetwórcą składają się z elementu transakcyjnego i elementu własnościowego, podczas gdy w podmiotach należących do inwestorów zewnętrznych relacje przetwórcy z dostawcami surowca mają jedynie charakter transakcyjny (Feng, Hendrikse, 2012). Podkreśla się, że spółdzielcza forma działalności pozwala tworzyć nowe rynki lub zapewniać dostęp do rynków swoim członkom, sprzyja zwiększeniu efektywności rynku czy ograniczeniu kosztów transakcyjnych (D' Amato, Festa, Dhir, Rossi, 2022). Badania największych spółdzielni na świecie, w tym sektora rolno-spożywczego, wskazują, że zachowują one płynność finansową i są rentowne (Zuba-Ciszewska, 2020a).…”
Section: Przegląd Literatury Przedmiotuunclassified
“…However, they pointed out the economic advantages linked to eliminating supply chain intermediaries [10]. Moreover, some scholars demonstrated that cooperatives are able to produce positive net economic results [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of cooperatives covers a significant part of the wine production sector [19]: for example, according to ISMEA [20], more than 55% of Italian wine production comes from cooperatives, which, therefore, could play a role in the improvement of wine farm sustainability [21,22]. The close relationships that cooperatives create with grape producers may support the change of farm practices, including supporting the adoption of more sustainable methods of grape growing, may enhance positive external social impacts [23] and may increase economic performance [11,24].…”
Section: Introductionmentioning
confidence: 99%